Pemberdayaan Pemandu Wisata dan Penguatan Tata Kelola untuk Pengembangan Sekolah Alam Bahasa Inggris Jetis - Agustinus Hary Setyawan; Nur Fachmi Budi Setyawan; Manuel O. Malonisio (Universitas Muhammadiyah Palembang, 2025)
This community service program aims to enhance the capacity of tour guides and strengthen organizational governance to support the development of the English Nature School in Jetis, Sumberejo, Tempel, Sleman, Yogyakarta. The program was carried out through a participatory approach involving local stakeholders and an international partner from Aklan State University, Philippines. The main activities included sociopragmatics-based English training for tour guides, organizational management training grounded in psychology to improve governance, and hands-on practice with international experts and foreign tourists. The results showed significant improvements in cross-cultural communication skills, the establishment of a more structured Standard Operating Procedures (SOP), and the creation of an international partnership network to ensure program sustainability. Strengthening human resource capacity and governance is expected to position Jetis as a competitive English-based educational tourism village.